Stimulus Prediction and Postural Reaction: Phase-Specific Modulation of Soleus H-Reflexes Is Related to Changes in Joint Kinematics and Segmental Strategy in Perturbed Upright Stance - Ritzmann, Ramona; Lee, Kyungsoo; Krause, Anne; Gollhofer, Albert; Freyler, Kathrin (Frontiers in Integrative Neuroscience, 2018)
Anticipation determines the timing and efficiency of human motor performance. This study aimed to evaluate the effect of stimulus anticipation on proactive (prior to the event) and reactive (after the event) postural adjustments in response to perturbations. Postural set was manipulated by providing either (i) predictable, (ii) unpredictable or (iii) cheated perturbations which require balance corrections to maintain postural stability. In 29 subjects, a protocol of anterior and posterior perturbations was applied for the conditions (i) - (iii). Center of pressure (COP) displacement, ankle, knee and hip joint kinematics and electromyographic activity (EMG) of the soleus (SOL) and tibialis anterior (TA) muscles were recorded prior (PRE) and after posterior perturbations. SOL H-reflexes at the peak of the short-, medium- and long-latency responses (SLR, MLR, LLR) were assessed. For conditions (i) to (iii) EMG activity and COP differed prior to perturbation onset (p < 0.05). After perturbation, results demonstrated a progressively increased H-reflex amplitude in the MLR and LLR (p < 0.05), delayed muscle activities (p < 0.05) and shifted activation patterns, with muscles of the proximal segment being more involved in the compensatory postural response (p < 0.05). COP displacements and ankle, knee and hip joint deflections progressively increased (p < 0.05). Neuromechanical coupling showed positive correlations for the anticipation-induced changes in EMG activity and H-reflex amplitude with that of COP displacement (p < 0.05). In conclusion, proactive and reactive postural responses indicated setting dependent modulations of segmental and phasic muscle activation. A shift to proximal muscle groups and facilitated late reflex responses compensating for cheated or unpredicted perturbations was found to recover a safe body equilibrium. In consideration of the phase-specific adaptation and its interrelationship to the kinematics, it suggested that changes in stimulus prediction challenged the central nervous system to appropriately counteract the higher postural challenges. The outcomes of this experiment are of functional relevance for experimental and training settings involving perturbation stimuli. These findings provide fundamental information of the mechanisms underlying postural adjustments in response to external perturbations.